2000
DOI: 10.1002/1096-9071(200010)62:2<257::aid-jmv19>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Role of interferon gamma in the pathogenesis of primary respiratory syncytial virus infection in BALB/c mice

Abstract: Immunologic mechanisms are thought to contribute to the pathogenesis of respiratory syncytial virus (RSV) bronchiolitis in humans. RSV-infected BALB/c mice exhibit tachypnea and signs of outflow obstruction, similar to symptoms in humans. Interferon gamma (IFNgamma) has been found to be the predominant cytokine produced in humans and mice with RSV infection. We therefore undertook this study to evaluate the role of IFNgamma in the development of respiratory illness in RSV-infected mice. BALB/c mice were infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
72
3

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 24 publications
14
72
3
Order By: Relevance
“…This finding contradicts an early report, which suggested that IFN-g might contribute to RSV-mediated AHR in mice (25); however, AHR was not documented in this study (e.g., by assessment of airway responsiveness to MCh) nor was the outcome of reinfection examined in IFN-g 2/2 mice. Durbin and colleagues compared the responses of IFN-g 2/2 and WT mice to primary RSV infection and found no differences in lung pathology, cytokine levels, or viral replication and rate of clearance between the two strains of mice even after inoculation with high doses of RSV (i.e., 10 7 PFUs [plaque-forming units]) (26).…”
Section: Discussioncontrasting
confidence: 99%
“…This finding contradicts an early report, which suggested that IFN-g might contribute to RSV-mediated AHR in mice (25); however, AHR was not documented in this study (e.g., by assessment of airway responsiveness to MCh) nor was the outcome of reinfection examined in IFN-g 2/2 mice. Durbin and colleagues compared the responses of IFN-g 2/2 and WT mice to primary RSV infection and found no differences in lung pathology, cytokine levels, or viral replication and rate of clearance between the two strains of mice even after inoculation with high doses of RSV (i.e., 10 7 PFUs [plaque-forming units]) (26).…”
Section: Discussioncontrasting
confidence: 99%
“…Nonetheless, in our experiments with either IFN-␥ Ϫ/Ϫ BALB/c or 129SvEv IFN-␥R Ϫ/Ϫ mice, eosinophils were present in infiltrates surrounding vessels and airways of infected lungs, but only at low levels. This observation has been made by others (24,39), who concluded, as we did, that RSV pathogenesis in IFN-␥-deficient animals is similar to that in wild-type animals. We therefore wondered whether, in the absence of IFN-␥, IFN-␣␤ could act in a compensatory manner to inhibit Th2 lymphocyte development and eosinophilic disease (7).…”
Section: Discussionsupporting
confidence: 89%
“…Constitutive BAL IL-18 concentration was significantly higher in Nrf 2 2/2 mice than in Nrf 2 1/1 mice, and IL-18 was significantly more elevated by RSV in Nrf 2 2/2 mice than in Nrf 2 1/1 mice after 5 days. BAL concentrations of the Th1 cytokine IFN-g in Nrf 2 1/1 mice were not significantly increased relative to controls until 7 days after RSV infection as shown in previous kinetic studies of murine RSV models (7,34), but lung IFN-g was not significantly increased at any time in Nrf 2 2/2 mice. Among BAL Th2 cytokines, IL-10 was not significantly changed in Nrf 2 1/1 mice but was significantly elevated in Nrf 2 2/ 2 mice at 7 days.…”
Section: Differential Pulmonary Cytokine Profiles After Rsv Infectionsupporting
confidence: 61%
“…Particularly in the clinical situation of RSV infection, many studies demonstrated that the Th1/Th2 cytokine balance in the serum of children with severe RSV disease was more skewed toward Th2 cytokines (4). In addition, IFN-g has been determined as a dominant host response factor for RSV clearance clinically and in animal studies (7,50). Therefore, a lack of IFN-g and Th2-skewed cytokine profile in Nrf 2 2/2 mice may explain their delayed viral clearance and support the enhanced RSV susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation